Impact Of Implementation and Operational Efficience on the Profitability of Indonesia's Principal Bank Period 2014-2023 - Nurul Annisa; Marliyah Marliyah; Tuti Anggraini (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The purpose of this article is to discuss the influence of problematic financing and operational efficiency on Bank Muamalat Indonesia's profitability for the 2014-2023 period. This article is a type of descriptive quantitative research. The research population is the financial report of Bank Muamalat Indonesia, while the research sample is the financial report of Bank Muamalat Indonesia for 2014-2023. The research data used is secondary data obtained from the official website using library study techniques. Next, the data was analyzed through descriptive tests, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The analysis findings state that problematic financing and operational efficiency have a significant influence on the profitability of PT Bank Muamalat Indonesia. The research results have implications for banks which must manage their assets wisely, especially in financing to minimize risks, streamline operational funds, and carry out controls in their applications, so that banks can get maximum profits.